2018
DOI: 10.1080/10942912.2018.1559187
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress involved in textural changes of sea cucumber Stichopus japonicus body wall during low-temperature treatment

Abstract: View related articles View Crossmark data Citing articles: 5 View citing articles Oxidative stress involved in textural changes of sea cucumber Stichopus japonicus body wall during low-temperature treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…The downregulation of these two genes (Bax inhibitor-1 and Src family kinase 5) further indicated that the original antiapoptosis mechanisms were damaged and irreversible apoptosis occurred in the cells of tenderized AJBW. These results were supported by our previous findings about the DNA damage and enhancement of caspase-3 activity in AJBW during tenderization [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The downregulation of these two genes (Bax inhibitor-1 and Src family kinase 5) further indicated that the original antiapoptosis mechanisms were damaged and irreversible apoptosis occurred in the cells of tenderized AJBW. These results were supported by our previous findings about the DNA damage and enhancement of caspase-3 activity in AJBW during tenderization [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies on marine animals, such as coral [ 37 ], pacific oyster [ 38 ], and marine snail [ 39 ], have reported that exposure to thermal stress can induce reactive oxygen species (ROS) accumulation following antioxidant defense mechanism. In our study, oxidant response genes, such as glutathione S-transferase (GST) and glutathione peroxidase (GPx), showed significant upregulated patterns ( Table 3 ), and superoxide dismutase, catalase, and microsomal GST decreased in AJBW during the heating period of 3 h. Similarly, we previously detected two times increment in signal intensity of ROS-derived radicals in T_1h vs CON [ 40 ]. Previous studies reported that the transcripts and activities of the antioxidant enzymes could be altered differently by temperature gradients combined with exposure periods [ 41 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 70%
“…During heating at 40 °C, the shrinkage rate in the axial direction is slower than that in the radial direction (Wang et al ., 2020). Finally, the hardness trend first increased to the maximum and then decreased gradually with heating time expended (Dong et al ., 2018). The storage modulus ( G ′) of samples decreased over time at 40 °C (Bi et al ., 2016).…”
Section: Physical Changes Of Sea Cucumber During Thermal Treatmentmentioning
confidence: 99%
“…Processed sea cucumbers are primarily divided into dried products (called ‘beche‐de‐mer’), pickled products and ready‐to‐eat products (Liu et al ., 2020b). Nonetheless, it has been suggested that some unique physiochemical makeup causes sea cucumber textural degradation during conventional thermal treatments (Dong et al ., 2018). To promote the textural and sensory characteristics of sea cucumber products, novel processing techniques have been developed, including high‐pressure steam (Peng et al ., 2015), low‐temperature treatment (Dong et al ., 2018), far‐infrared radiation drying (Moon et al ., 2017) and generation of 3D printed recombinant product (Yu et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies have reported the effect of thermal treatment on collagen fibrils in relation to oxidation [ 139 ]. A recent study investigated the molecular structure of collagen isolated from Apostichopus japonicus during thermal treatment in the presence of (-)-epigallocatechin gallate (EGCG) [ 105 ] and demonstrated that EGCG has the potential to enhance the thermal stability of crude collagen fibrils by neutralizing the effect of heat-induced radicals (hydroxyl radical) and protect the macromolecular structure of crude collagen in a dose-dependent manner [ 105 ].…”
Section: Characteristics and Properties Of Collagen Type Imentioning
confidence: 99%